2005
DOI: 10.1111/j.0022-202x.2005.23972.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Epidermal Structure in Mice with Temporally Controlled Fatp4 Deficiency

Abstract: So far, little is known about the physiological role of fatty acid transport protein 4 (Fatp4, Slc27a4). Mice with a targeted disruption of the Fatp4 gene display features of a human neonatally lethal restrictive dermopathy with a hyperproliferative hyperkeratosis, a disturbed epidermal barrier, a flat dermal-epidermal junction, a reduced number of pilo-sebaceous structures, and a compact dermis, demonstrating that Fatp4 is necessary for the formation of the epidermal barrier. Because Fatp4 is widely expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 31 publications
(54 reference statements)
4
44
0
Order By: Relevance
“…In contrast, Herrmann et al (6) found FATP4 expression only in the granular layer of newborn mice, when the hair follicles are beginning to develop and sebocytes are not yet differentiated. Our data are in closer agreement with those of Herrmann et al (12), as we observed FATP4 expression primarily in suprabasal keratinocytes. We have detected FATP4 in the dermis, although it is only barely detectable, and the staining is inconsistent.…”
Section: Fatp4supporting
confidence: 94%
See 3 more Smart Citations
“…In contrast, Herrmann et al (6) found FATP4 expression only in the granular layer of newborn mice, when the hair follicles are beginning to develop and sebocytes are not yet differentiated. Our data are in closer agreement with those of Herrmann et al (12), as we observed FATP4 expression primarily in suprabasal keratinocytes. We have detected FATP4 in the dermis, although it is only barely detectable, and the staining is inconsistent.…”
Section: Fatp4supporting
confidence: 94%
“…We not only showed that FATP4 expression in the epidermis during development can rescue the mutation, but we further showed that FATP4 is only critical in the granular layer, and therefore it is likely to be crucial for initial barrier formation. But similar to the findings of Herrmann et al (12), we did observe areas of thickened epidermis in older Miw-Fatp4 rescued mutants by histological analysis, although the mice appeared overtly normal. This is likely because of decreased expression of the transgene in nonmuscle lineages (including skin) postnatally, which we have consistently observed in transgenic mouse studies that utilize the Miw regulatory element.…”
Section: Fatp4supporting
confidence: 91%
See 2 more Smart Citations
“…FATP4 null mice displayed features of a human neonatally lethal restrictive dermopathy that has been associated with a disturbed function in the epidermal barrier (18)(19)(20). FATP4 encodes an ACSL with substrate specificity to very LCFAs that may be required for the synthesis of lipids crucial in the formation of a healthy epidermis (21,22). Polymorphisms in the human FATP4 gene locus have identified this gene as a candidate for the insulin resistance syndrome (23).…”
mentioning
confidence: 99%